Hydractinia, a pioneering model for stem cell biology and reprogramming somatic cells to pluripotency - Plickert, Günter; Frank, Uri; Müller, Werner A. (The international journal of developmental biology, 2012)
Hydractinia, a representative marine colonial hydroid, was the first organism in the history of biology in which migratory precursors of germ cells were described and termed “stem cells” (Weismann, 1883). These stem cells, now known as interstitial cells (i-cells), are thought to remain pluripotent throughout their life. Using animals depleted of their own stem cells and repopulated with allogeneic mutant donor stem cells, it was shown that Hydractinia i-cells differentiate into any cell type including epithelial cells and germ cells that express germ line markers such as Vasa, Piwi and Nanos. In Hydra, i-cells also provide germ cells and somatic cells with the exception of epithelial cells. The latter derive from two subpopulations of differentiated epithelial cells with self-renewal capacity. In Hydractinia, forced expression of the Oct4-like transcription factor, Polynem (Pln), in ep-ithelial cells transforms them into stem cells that develop neoplasms. I-cells express the Wnt-receptor Frizzled and are Wnt responsive. Activation of Wnt signaling induces the production of numerous nematocytes (stinging cells) and nerve cells. In parallel, supernumerary tentacles develop. I-cells also express Myc and Nanos. Their misexpression causes severe developmental defects. Hydractinia polyp buds arise from aggregating stem cells, in contrast to Hydra buds, which derive from evaginating epithelial cells. Wnt activation increases budding frequency and the emergence of ectopic head structures. The potential of stem cells to invade neighbors may have provided selection pressure for the evolution of allorecognition and histo-incompatibility. Hence, Hydractinia have now attained the posi-tion of a powerful model in stem cell research, axis formation and allorecognition.